Patent ductus arteriosus closure using an Amplatzer(™) ventricular septal defect closure device - Fernando, Rajeev (Pulsus Group Inc, 2013)
The ductus arteriosus originates from the persistence of the distal portion of the left sixth aortic arch. It connects the descending aorta (immediately distal to the left subclavian artery) to the roof of the main pulmonary artery, near the origin of the left pulmonary artery. Persistence of the duct beyond 48 h after birth is abnormal and results in patent ductus arteriosus (PDA). PDA is rare in adults because it is usually discovered and treated in childhood. Mechanical closure remains the definitive therapy because the patency of ductus arteriosus may lead to multiple complications, depending on the size and flow through the ductus. PDA closure is indicated in patients with symptoms and evidence of left heart enlargement, and in patients with elevated pulmonary pressures when reversal is possible. Transcatheter closure is the preferred technique in adults because it avoids sternotomy, reduces the length of hospital stay and is associated with fewer complications compared with surgery. First demonstrated in 1967, both the technique and the occluder devices used have since evolved. However, designing an ideal PDA occluder has been a challenge due to the variability in size, shape and orientation of PDAs. The present article describes a case involving a 35-year-old woman who presented to the Center for Advanced Heart Failure (Houston, USA) with congestive heart failure due to a large PDA, which was successfully occluded using an Amplatzer (St Jude Medical, USA) muscular ventricular septal defect closure device. The wider waist and dual-retention discs of these ventricular septal defect closure devices may be important factors to consider in the future development of devices for the occlusion of large PDAs.